ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN HASIL HUTAN BUKAN KAYU (HHBK) AKAR ANGIN (Usnea barbata) DI HUTAN LINDUNG MUTIS TIMAU (Studi Kasus di Desa Kuan Noel dan Desa Fatumnasi, Kecamatan Fatumnasi, Kabupaten Timor Tengah Selatan) - Aryanto Albert Besi; I Nyoman W Mahayasa; Nixon Rammang (Wana Lestari, 2021)
Kuan Noel and Fatumnasi Villages are villages that have a lot of potential for Beard lichen (Usnea barbata) as one of their main sources of income. This means that the sustainability and development of beard lichen are the main keys in ensuring the production, utilization and development of beard lichen, it is necessary to conduct a study or research. This study aims to determine the Potential and Development Strategy of Non-Timber Forest Products (NTFPs) Beard lichen. The number of respondents in this study were 133 beneficiary respondents beard lichen randomly selected in two sample population villages. Data collection was carried out by observation, observation, interviews and literature study. The data collected was then analyzed descriptively and analyzed using the SWOT method. The results showed that the distribution of beard lichen or in the local language hau konof in the research location was spread wildly on the ampupu tree (Eucalyptus urophylla) and needed high humidity for its life. The use of beard lichen at the research location is only collected for sale to collectors. In the harvesting activity, one tree has the potential of beard lichen that can produce 3-5 kg ​​of wet beard lichen. Collection of beard lichen in a day ranges from 5-10 kg and in a period of 1 week can collect 30-70 kg of beard lichen. The process of collecting beard lichen begins with preparing a number of tools to use, such as sacks and bamboo. Beard lichen harvesting must ensure that beard lichen are dry. Beard lichen collected in wet conditions can cause damage which is indicated by a change in the color of beard lichen to yellow or reddish when stored for too long. Based on IFAS and EFAS, the following calculations are made: Total strengths and opportunities (S + O) = 2.70 + 2.76 = 5.46; The number of weaknesses and opportunities (W + O) = 2.06 + 2.76 = 4.82; Total force and threat (S + T) = 2.70+ 1.3 = 4; The number of weaknesses and threats (W + T) = 2.06 + 1.3 = 3.36. Based on the results of research and SWOT analysis, the strategic position is the development of community empowerment through the formation of social forestry in the utilization and management of beard lichen.